Patients requiring an acute operation: where are the delays in the process?. Issue 9 (8th July 2018) - de Burlet, Kirsten J.; Desmond, Brendan; Harper, Simon J.; Larsen, Peter D.; Dennett, Elizabeth R.
Abstract : Background: Delays to surgery for patients requiring an acute operation are associated with increased morbidity and mortality. A recent study from our institution observed long waiting times for patients booked for an acute operation. The aim of this study was to evaluate the patient's progress from presentation to arrival in the operating theatre and to identify where delays occurred. Methods: Patients undergoing acute general surgery between July 2016 and May 2017 were studied. Data were obtained for time of presentation, imaging, theatre and booking. A time interval from presentation to booking for theatre of greater than 6 h was defined as a diagnostic delay. A time interval from booking to theatre greater than the category defined time (four‐level priority system) was defined as a logistic delay. Results: A total of 683 patients were included. A diagnostic delay was observed in 55.1%. This occurred more frequently in patients who required imaging prior to their operation (82.5 versus 41.1%, P < 0.001). Logistic delay occurred in 31.0% of the patients, and this was most common for patients booked as a category 3 (requiring surgery within 6 h, 41.8%, P < 0.001). Patients who had a diagnostic delay were significantly more likely to have a post‐operative complication compared to patients who did not (17.2 versus 10.0%, P = 0.009). Conclusion: There are significant delays associated with patients presenting to the acute general surgery service and their transition to theatre. Addressing both the diagnostic and the logistic delays in our institution should result in a significant improvement in patient care.